Environmental conditions at arrival to the wintering grounds and during spring migration affect population dynamics of barn swallows Hirundo rustica breeding in Northern Italy. Issue 1 (10th December 2015) - Sicurella, Beatrice; Musitelli, Federica; Rubolini, Diego; Saino, Nicola; Ambrosini, Roberto
Abstract: Several populations of long‐distance migratory birds are currently suffering steep demographic declines. The identification of the causes of such declines is difficult because population changes may be driven by events occurring in distant geographical areas during different phases of the annual life‐cycle of migrants. Furthermore, wintering areas and migration routes of populations of small‐sized species are still largely unknown, with few exceptions. In this paper we identified the critical phases of the annual life‐cycle that most influence the population dynamics of a small passerine, the Barn Swallow Hirundo rustica. We used information on temporal dynamics of a population breeding in Northern Italy, whose wintering range and timing of migration have been recently described by miniaturised tracking dataloggers. Our results indicated that primary productivity in the wintering grounds in the month when most individuals arrive from autumn migration and primary productivity in an area that is probably a stopover site during spring migration, influenced population dynamics more than habitat conditions at the breeding grounds. By using annual variation in primary productivity at the wintering grounds and stopover sites as predictors, we replicated the observed interannual population changes with great accuracy. However, the steep decline recently suffered by the population could be replicated only by including a constant annual decline in the model, suggesting that changes in primary productivity only predicted the interannual variation around the long‐term trend. Our study therefore suggests the existence of critical periods during wintering and migration that may have large impact on population fluctuations of migrant birds.